Impact of the COVID-19 era on preventative primary care for children 0–5 years old: a scoping review - Helen Valkanas; Kimberley McFadden; Isabella Mignacca; Xin Qi; Mackenzie Jordan; Imaan Bayoumi; Patricia Li (BMC Primary Care)
Abstract Background Restrictions to routine preventative primary care well child visits (WCV) during COVID-19 may have affected a variety of outcomes for young children including growth, development, and the identification and management of developmental delays. To better understand the effect of the pandemic on these outcomes, we conducted a scoping review of studies published between March 2020 and April 2024. The objectives of this scoping review were to determine the impact of the COVID-19 era on WCV attendance and developmental outcomes in children 0–5 years old. Results 23 articles met inclusion criteria. Most studies were conducted in the U.S. The overall COVID-19 era WCV rate was lower compared to pre-COVID visit rates. Higher rates of missed WCVs and reduced access were reported for racialized children and those from families with lower socioeconomic status. Studies measuring developmental outcomes found associations between children born during the pandemic and increased rates of expressive language delays, decreased personal-social skills, increased delays in achieving verbal, motor, and overall cognitive performance milestones, increased externalizing behaviours, and decreased prosocial behaviour. No study examined the impact of WCV attendance rates on developmental outcomes. Conclusions During the COVID-19 pandemic, infants, toddlers, and young children attended fewer preventative primary care visits and pandemic-born children were more likely to show signs of developmental delay. This review highlights the need for further research to better understand the longitudinal impact of reduced access to preventative primary care and child health outcomes, including the early detection of, and referral for, developmental delays.